Brain Amyloid Burden and Resting-State Functional Connectivity in Late Middle-Aged Hispanics - Tahmi, Mouna; Rippon, Brady; Palta, Priya; Soto, Luisa; Ceballos, Fernando; Pardo, Michelle; Sherwood, Greysi; Hernandez, Gabriela; Arevalo, Rodolfo; He, Hengda; Sedaghat, Amirreza; Arabshahi, Soroush; et al. (Frontiers in Neurology, 2020)
Non-linear relations of brain amyloid beta (Aβ) with task- based functional connectivity (tbFC) measured with functional magnetic resonance imaging (fMRI) have been reported in late middle age. Our objective was to examine the association between brain Aβ and resting-state functional connectivity (rsFC) in late middle-aged adults. Global brain Aβ burden was ascertained with 18F-Florbetaben Positron Emission Tomography (PET); rsFC was ascertained on 3T Magnetic Resonance Imaging (MRI) among 333 late middle-aged Hispanics adults without dementia in four major brain functional connectivity networks: default mode network (DMN), fronto-parietal control network (FPC), salience network (SAL) and dorsal attention network (DAN). We examined the relationship of global brain Aβ with rsFC using multivariable linear regression adjusted for age, sex, education, and APOE-4 genotype. We quantified the non-linear associations both with quadratic terms and by categorizing Aβ into three groups: low Aβ, intermediate Aβ, and positive Aβ. We found no significant linear or non-linear associations between Aβ, measured either continuously or categorically, with rsFC in the examined networks. Our null findings may be explained by the younger age of our participants in whom amyloid burden is relatively low. It is also possible that the recently reported non-linear relationship is exclusive to task fMRI and not rsfMRI.